2018
DOI: 10.1097/aog.0000000000002595
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and Peripartum Outcomes in Vanishing Twin Pregnancies Achieved by In Vitro Fertilization

Abstract: In pregnancies conceived by in vitro fertilization that progress to at least 24 weeks of gestation, vanishing twin and singleton pregnancies had similar perinatal and peripartum outcomes. Both were significantly better than twin pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 28 publications
0
26
1
Order By: Relevance
“…Besides, it is also suggested in previous results that, the early death of a pair of twins may improve the pregnancy outcomes. But there may be more adverse complications when continuing the twin pregnancy [20]. Analysis by Timur H et al indicated that VTS patients were more likely to develop LBW, very low birthweight (VLBW), intrauterine growth restriction and pre-eclampsia [2123].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is also suggested in previous results that, the early death of a pair of twins may improve the pregnancy outcomes. But there may be more adverse complications when continuing the twin pregnancy [20]. Analysis by Timur H et al indicated that VTS patients were more likely to develop LBW, very low birthweight (VLBW), intrauterine growth restriction and pre-eclampsia [2123].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, blood flow towards the surviving twin might be decreased temporarily, inducing a relative placental insufficiency, which could delay placental expansion and retard fetal growth. Interestingly, we did not find that the vanishing fetus had any significant influence on the rate of preterm birth either in the IVF/ICSI group or in the spontaneous group, a result which contrasts with other epidemiological and observational studies [28], [34], but confirms still other studies [22], [27], [63]. In relation to low birth weight and preterm birth, the perinatal outcome of VT after ART has been found similar to singletons and better than twin pregnancies in other retrospective studies [63], [64].…”
Section: Discussion Of Specific Results and Comparison With Other Studiescontrasting
confidence: 90%
“…A few studies reported an increased risk of preterm birth before 37 weeks [3,6,15], 34 weeks [5,6], 32 weeks [3,15] and 28 weeks [5] of gestation. However, La Sala and Phillip reported that the preterm birth was not increased in vanishing twin [7,11]. Recently, a meta-analysis of the obstetric outcome of vanishing twin has been performed [16], and preterm birth less than 34 weeks was significantly increased in vanishing twin group.…”
Section: Plos Onementioning
confidence: 97%
“…Traditionally, it was believed that this vanishing twin phenomenon do not affect the pregnancy outcomes of the remained co-twin [4]. However, a few recent studies described adverse obstetric outcomes such as preterm birth and low birth weight in vanishing twin [5][6][7][8][9], whereas other studies did not find differences between singleton pregnancy and vanishing twin [7,10,11]. In addition, there is a paucity of information regarding the risk of spontaneous preterm birth (sPTB) and indicated spontaneous preterm birth (iPTB) although it is plausible that vanishing twin might increase the risk of sPTB by an inflammatory condition [12].…”
Section: Introductionmentioning
confidence: 99%